Evaluasi Kinerja Website E-Procurement Pada PT XYZ Di Surabaya Berbasis ISO 25010 - Cahyani Fitonah, Rizki; Ardilla, Yunita; Ridwan, Mujib; Teguh Wibowo, Achmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Digital transformation drives the adoption of e-procurement systems as a strategic instrument for enhancing efficiency, transparency, and corporate governance. However, the realization of these benefits is critically dependent on the technical performance and reliability of the system in use. This study aims to conduct a quantitative evaluation of the performance and reliability of the e-procurement website belonging to PT XYZ, a private company in Surabaya, utilizing the international software quality standard framework ISO/IEC 25010. The primary contribution of this study lies in the methodological synthesis that maps empirical performance metrics generated via load testing with Apache JMeter onto the characteristics of Performance Efficiency and Reliability. The testing was conducted on two critical transactional scenarios, namely new user registration and login, with varying virtual user loads (10, 50, and 100 users). The metrics analyzed included response time, throughput, and error rate. The test results indicated that the system exhibited excellent time-behaviour in the login scenario, with an average response time of 562 ms under a 100-user load, which falls within the